2022
DOI: 10.23887/jisd.v6i1.43579
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Acceptance of Kumandang Interactive Reading Aloud Smartphone-Based Apps

Abstract: In 21st century learning, the development of smartphone-based applications to support education, especially literacy, has become a basic need. This study aims to analyze the factors that factor in user acceptance of an Android-based application called Kumandang, Reading Aloud Activities. This type of research is survey research. The subjects of this study were ninety participants consisting of teachers, parents, and guardians. The research instrument used in this study was a questionnaire sheet. The technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Researchers have inquired about several factors that contribute to learners' acceptance of language learning technology related to self-efficacy, attitude, self-regulated learning and learning motivation [2], perceived enjoyment, satisfaction, perceived risk moderators and trust [4], perceived anxiety and use behaviour [5], and behavioural intentions habits [6]. Further study revealed that English as Foreign Language (EFL) learners' acceptance of technology in mobile-based flipped teaching was detected, and it was discovered that attitude and behavioural attention played a pivotal role in affecting learners' acceptance of the technology [7].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have inquired about several factors that contribute to learners' acceptance of language learning technology related to self-efficacy, attitude, self-regulated learning and learning motivation [2], perceived enjoyment, satisfaction, perceived risk moderators and trust [4], perceived anxiety and use behaviour [5], and behavioural intentions habits [6]. Further study revealed that English as Foreign Language (EFL) learners' acceptance of technology in mobile-based flipped teaching was detected, and it was discovered that attitude and behavioural attention played a pivotal role in affecting learners' acceptance of the technology [7].…”
Section: Introductionmentioning
confidence: 99%